2021
DOI: 10.1523/eneuro.0041-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation above the Medial Prefrontal Cortex Facilitates Decision-Making following Periods of Low Outcome Controllability

Abstract: Visual Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
(87 reference statements)
0
7
1
Order By: Relevance
“…The important role of ACC in HIV brain disease is supported by neurobehavioral and brain imaging studies in HIV: first, ACC injury in PWH has been detected using various brain imaging techniques, including structural MRI [ 17 ], task-based functional MRI (fMRI) [ 18 ], task-free fMRI [ 19 ] and perfusion MRI [ 20 ], proton magnetic resonance spectroscopy (MRS) [ 3 , 21 23 ], and positron emission tomography (PET) [ 20 , 24 ]; second, the high prevalence of executive deficits [ 25 ] and apathy [ 26 ]—both are known to involve the ACC [ 27 29 ]—provides additional evidence supporting the prevalence and importance of ACC injury in PWH. Furthermore, using invasive and non-invasive brain stimulation techniques (including deep brain stimulation, repetitive transcranial magnetic stimulation (rTMS), and tDCS), previous studies provided evidence suggesting that dACC stimulation might be effective in modulating brain/cognitive function [ 30 33 ] and emotional processes [ 34 ], as well as in treating disorders like obsessive compulsive disorder [ 35 , 36 ]. Highly relevant to the present study, two previous studies found that one session of anodal tDCS stimulation (1.5–2 mA, 15–20 minutes) targeting the dACC was sufficient to induce detectable changes at a behavioral (“more efficient adjustments in decision‐making strategies” [ 33 ]) or neural level (neuronal signal related to “improved efficiency of neural resources for inhibitory control and error processing” [ 32 ]), providing further support for the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important role of ACC in HIV brain disease is supported by neurobehavioral and brain imaging studies in HIV: first, ACC injury in PWH has been detected using various brain imaging techniques, including structural MRI [ 17 ], task-based functional MRI (fMRI) [ 18 ], task-free fMRI [ 19 ] and perfusion MRI [ 20 ], proton magnetic resonance spectroscopy (MRS) [ 3 , 21 23 ], and positron emission tomography (PET) [ 20 , 24 ]; second, the high prevalence of executive deficits [ 25 ] and apathy [ 26 ]—both are known to involve the ACC [ 27 29 ]—provides additional evidence supporting the prevalence and importance of ACC injury in PWH. Furthermore, using invasive and non-invasive brain stimulation techniques (including deep brain stimulation, repetitive transcranial magnetic stimulation (rTMS), and tDCS), previous studies provided evidence suggesting that dACC stimulation might be effective in modulating brain/cognitive function [ 30 33 ] and emotional processes [ 34 ], as well as in treating disorders like obsessive compulsive disorder [ 35 , 36 ]. Highly relevant to the present study, two previous studies found that one session of anodal tDCS stimulation (1.5–2 mA, 15–20 minutes) targeting the dACC was sufficient to induce detectable changes at a behavioral (“more efficient adjustments in decision‐making strategies” [ 33 ]) or neural level (neuronal signal related to “improved efficiency of neural resources for inhibitory control and error processing” [ 32 ]), providing further support for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using invasive and non-invasive brain stimulation techniques (including deep brain stimulation, repetitive transcranial magnetic stimulation (rTMS), and tDCS), previous studies provided evidence suggesting that dACC stimulation might be effective in modulating brain/cognitive function [ 30 33 ] and emotional processes [ 34 ], as well as in treating disorders like obsessive compulsive disorder [ 35 , 36 ]. Highly relevant to the present study, two previous studies found that one session of anodal tDCS stimulation (1.5–2 mA, 15–20 minutes) targeting the dACC was sufficient to induce detectable changes at a behavioral (“more efficient adjustments in decision‐making strategies” [ 33 ]) or neural level (neuronal signal related to “improved efficiency of neural resources for inhibitory control and error processing” [ 32 ]), providing further support for the present study. The posterior cingulate cortex (PCC) was selected as the secondary target region, as the PCC is a central hub of the default mode network (DMN) and both PCC and DMN have been frequently implicated in various neurodegenerative diseases [ 37 , 38 ], including HAND [ 19 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rare outcome (20% of the trials) was the card’s feedback for the complementary action. In contrast with earlier studies ( 14 , 17 , 26 ), we decided to increase the contingency level in the controllable blocks to 80/20% (compared to the original 70/30%) in order to contrast the “control” vs. “no control” blocks even further. During the second block, rewards were delivered at random (response-feedback contingency was set to 50/50%).…”
Section: Methodsmentioning
confidence: 99%
“…Computational modeling of the cortical distribution of the tDCS-induced electric field on realistic head models ( 27 ) confirmed that this montage provides relatively focused stimulation of the mPFC/dACC ( 28 ). In addition, this montage was identical to the one used in a previous study that resulted in improved value-based choices following manipulations of reward/loss controllability for active vs. sham HD-tDCS ( 26 ). Active stimulation consisted of a 30-s ramp-up, 15 min stimulation, and 30-s ramp-down.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation